Integrated Two‐Analyte Population Pharmacokinetic Model of Polatuzumab Vedotin in Patients With Non‐Hodgkin Lymphoma. (23rd December 2019) - Lu, Dan; Lu, Tong; Gibiansky, Leonid; Li, Xiaobin; Li, Chunze; Agarwal, Priya; Shemesh, Colby S.; Shi, Rong; Dere, Randall C.; Hirata, Jamie; Miles, Dale; Chanu, Pascal; et al.
Abstract : A two‐analyte integrated population pharmacokinetic (PK) model that simultaneously describes concentrations of antibody‐conjugated monomethyl auristatin E (acMMAE) and unconjugated MMAE following repeated administrations of polatuzumab vedotin (pola) was developed based on data from four clinical studies of pola in patients with non‐Hodgkin lymphoma. A two‐compartment model with a nonspecific, time‐dependent linear clearance, a linear time‐dependent exponentially declining clearance, and a Michaelis–Menten clearance provided a good fit of the acMMAE plasma PK profiles. All three acMMAE elimination pathways contributed to the input to the central compartment of unconjugated MMAE, which was also described by a two‐compartment model. Population PK parameters, covariate effects, and interindividual variability of model parameters were estimated. The impact of clinically relevant covariates on PK exposures of each analyte were quantified and reported to support key label claims.